Energy performance and thermo-economic assessment of a microturbine-based dual-fuel gas-biomass trigeneration system - Pantaleo,AM; Camporeale,SM; Markides,CN; Mugnozza,GS; Shah,N (Elsevier, 2017)
The focus of this paper is on the energy performance and thermo-economic assessment of a small scale (100 kWe) combined cooling, heat and power (CCHP) plant serving a tertiary/residential energy demand fired by natural gas and solid biomass. The plant is based on a modified regenerative micro gas-turbine (MGT), where compressed air exiting the recuperator is externally heated by the hot gases produced in a biomass furnace. The flue gases after the recuperator flow through a heat recovery system (HRS), producing domestic hot water (DHW) at 90 °C, space heating (SH), and also chilled water (CW) by means of an absorption chiller (AC). Different biomass/natural gas ratios and an aggregate of residential end-users in cold, average and mild climate conditions are compared in the thermo-economic assessment, in order to assess the trade-offs between: (i) the lower energy conversion efficiency and higher investment cost when increasing the biomass input rate; (ii) the higher primary energy savings and revenues from feed-in tariffs available for biomass electricity exported into the grid; and (iii) the improved energy performance, sales revenue and higher investment and operational costs of trigeneration. The results allow for a comparison of the energy performance and investment profitability of the selected system configuration, as a function of the heating/cooling demand intensity, and report a global energy efficiency in the range of 25-45%, and IRR in the range of 15-20% assuming the Italian subsidy framework.